Formation of Marketing Strategy for Sustainable Development of Enterprises in the Domestic Market - Marta Kopytko, Inna Boychuk, Ulyana Balyk, Nataliia Mykhailyk and Pavlo Hryhoruk (Review of Economics and Finance by REF Press UK, 2023)
The main purpose of the article is to determine the optimal marketing strategy for a single group of enterprises in the domestic market. The object of the study is the sustainable development of enterprises in the domestic market. The scientific task is to determine indicators and calculate the state of enterprises in the domestic market for the further formation of their marketing strategy. The research methodology involves the use of modern mathematical methods. As a result of the calculations, it was possible to establish the state of sustainable development of the enterprise in the domestic market. The innovativeness of the obtained results is revealed in the methodical approach itself and how it is possible to first assess the state of sustainable development of the enterprise in the domestic market, and then choose the optimal marketing strategy based on the results of the analysis. The study is limited by taking into account the specifics of only the domestic market for bee products and the related marketing strategy of Polish enterprises. The consequence of such limitations is that it is not possible to talk about the universality of the proposed research results. Prospects for further research should include the application of the proposed methodological approach for the entire EU market, that is, the external one. This is necessary given that honey and bee products are poor only within the domestic market.
Review of Economics and Finance. - Vol. 21. - No. 1. - Pp. 2271-2278. - 2023
Keywords: Sustainable Development; marketing; strategy; enterprises; market; economy